Refusão superficial a laser da liga com memória de forma Cu-11,8Al-3,2Ni-3Mn (% Peso) - Silva, Murillo Romero da (Universidade Federal de São Carlos, 2017)
Shape memory alloys (SMA) are alloys that undergo martensitic transformation due to an external solicitation (temperature, stress, strain or magnetic field) and are capable of recovering permanent deformation when heated above a critical temperature. The most used shape memory alloys are Ti-Ni- and Cu-based. Cu-based SMA have some advantages due to better thermal and electrical conductivity, lower production cost and are easier to process. The main disadvantage of Cu-based SMA is its low ductility. This property is improved by decreasing the grain size and by a reduction of microstructural heterogeneities. This can be achieved at the surface of structural components after LASER remelting, through which the surface of the material is remelted by a LASER beam and solidifies under extremely high cooling rates. In this context, the aim of the present work is to investigate the influence of LASER surface remelting in the microstructure, thermal stability and mechanical properties of Cu-11.8Al-3.2Ni-3Mn (wt. %) SMA plates obtained by suction casting. The samples were characterized by optical and scanning electron microscopy, energy dispersive X-ray spectroscopy, electron backscatter diffraction, X-ray computed tomography, X-ray diffraction, differential scanning calorimetry as well as by tensile and microhardness tests. The results show that small shifts in the transformation temperatures occur due to the LASER treatment. It was observed that only the monoclinic β’1 martensitic phase formed in the as cast and LASER treated samples. The LASER treatment provided an improvement in mechanical properties with an increase of up to 162 MPa in fracture stress, up to 2.2% in fracture strain and up to 21 HV in microhardness when compared with the as-cast sample. This makes the surface remelting treatment a promising method for improving the mechanical properties of Cu-based SMA.
Laser surface remelting of a Cu-11.8Al-3.2Ni-3Mn (wt. %) shape memory alloy
Keywords: Ligas com memória de forma; Refusão superficial a laser; Transformação martensítica; Resfriamento rápido; Shape memory alloys; Laser surface remelting; Martensitic transformation; Rapid cooling; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA